Clinical evaluation of hearing loss in type 2 diabetes mellitus: A prospective observational study - Shakya, Abishesh; Regmi Chalise, Sangita; Simkhada, Suman; Thapa, Jeegyasha; Khadka, Subash; Bhatta, Rishi; Khadgi, Ashish; Kumar, Binay; Parajuli, Ramesh; Shakya, Sujyoti (Journal of Chitwan Medical College, 2024)
Background: Diabetes mellitus (DM) is associated with many consequences because of chronic hyperglycemia, including hearing impairment due to damage to small blood vessels and nerves in the auditory system. This study aims to assess the grade of hearing loss in patients with Type 2 DM.Method: A prospective observational study was conducted at KISTMCTH from Dec 2022 to Jun 2023. Ninety-five patients with Type 2 DM who consented were included. Ethical approval was obtained. Patients with mental illness, family deafness history, noise exposure, and ototoxic medication were excluded. Routine ENT examinations, audiological and blood sugar evaluations were done. Hearing loss was classified according to WHO grading. Data analysis was done using SPSS, Pearson’s correlation and Fischer’s exact test to assess links between diabetes duration, glycaemic control, and hearing loss (p10 years. Hearing loss (91%) was observed in patients with poor glycaemic control (HbA1c >7). A significant correlation between hearing loss, glycaemic control, and duration of DM was found (p